Pertimbangan Hukum Hakim Mengenai Kompetensi Absolut Peradilan Tata Usaha Negara Dalam Menyelesaikan Permohonan Fiktif Positif Pada Putusan No. 3/P/FP/2020/PTUN.MKS - Indrana, Bagas Satya (UNES Law Review, 2024)
This research analyzes the Makassar State Administrative Court Decision No. 3/P/FP/2020/PTUN.MKS which will discuss the object of the petition regarding the positive fictitious decision of the Respondent who did not respond to the Petitioner's letter regarding IUPSWA. This application was registered on December 16, 2020 and decided on January 25, 2021 after the enactment of Law No. 11 of 2020 on Job Creation. Although the Law came into force on November 2, 2020, the decision did not consider the provisions of Article 175 Number 6 of Law No. 11 of 2020. In this case, the Panel of Judges relied more on Article 53 of Law No. 30 of 2014 on Government Administration, without taking into account the changes brought about by Article 175 Point 6 of Law No. 11 of 2020. The petitioner succeeded in filing the petition in its entirety, as the Panel of Judges was of the opinion that the Administrative Court was still authorized to handle cases of positive fictitious petitions. The reference basis for the absolute competence of the PTUN used by the Panel of Judges in adjudicating the application is based on the provisions of Article 53 of Law No. 30 of 2014 to Obtain a Decision on the Receipt of an Application to obtain a Decision and/or Action of a Government Agency or Official.